Approaches to quality assurance in school-based career development: policymaker perspectives from Australia. Issue 1 (2nd January 2022) - Rice, Suzanne; Hooley, Tristram; Crebbin, Sue
ABSTRACT: In this article we explore Australian policymaker perspectives on the quality assurance of career development (CD) programmes in schools. We found that Australian policymakers are concerned about the quality of CD provision in schools and have a wide range of approaches that they deploy to ensure and assure quality at the school level. Quality assurance within the country is focused on the qualifications and professionalism of the people delivering career development programmes rather than on systemic or organisational quality. We also found that the range of quality assurance tools that are deployed by such policymakers varies across the different Australian jurisdictions and is influenced by geography, the size of the jurisdiction and the level of priority given to career guidance.